175k views
0 votes
If f(x) =x^2 -2x and g(x) = 6x+4 for which value of c does (f+g)(x)=0

1 Answer

5 votes

Answer:

c = -2

Explanation:

The two functions are given as:

f(x) = x^2 - 2x

g(x) = 6x + 4

To find:

(f+g)(x) = 0

We can evaluate (f+g)(x) using the given functions.

We know that:

(f+g)(x) = f(x) + g(x)

= x²- 2x + 6x + 4

= x² + 4x + 4

Now, we have for x = c:

c² + 4c + 4 = 0

x² + 2c + 2c + 4 = 0

c(c+2) + 2(c+2) = 0

(c+2)² = 0

c+2 = 0

c = -2

User Doldt
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.